Development of DILETA: A Digital-Based Ethical Dilemma Simulation Application for Interactive Character Education Learning for Children - Kurniati Rahmadani; Popi Dayurni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study aims to develop and test the feasibility, practicality, and effectiveness of the DILETA (Ethical Dilemma) application as a digital-based interactive learning media for early childhood character education. The study used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects included five teachers in the needs analysis stage, six expert validators (media, language, materials), 20 early childhood education teachers in Focus Group Discussions (FGD), and 15 early childhood education in limited trials. The research instruments consisted of validation forms, FGD guides, and observation sheets based on the Child Development Achievement Level Standards (STPPA) according to Permendikbud No. 137 of 2014. Expert validation results showed an average score of 88.5%, categorized as very adequate. Teacher responses through FGDs obtained an average of 81.6%, categorized as very good, with the highest scores for aspects of narratives that are easy for children to understand (92.5%) and media utilization for class discussions (92.5%). Effectiveness testing through observations of 15 children resulted in an average score of 77.7%, categorized as positive. Children were more consistent in understanding religious and nationalistic values, while integrity values still require reinforcement through habituation and teacher guidance. Overall, the research concluded that the DILETA app is feasible, practical, and effective as a character education tool for early childhood. This tool has the potential to become a digital innovation in supporting the strengthening of character education in accordance with early childhood development standards.